Cornual abscess rupture: A rare etiology of acute abdomen. Issue 12 (18th October 2018) - Patil, Pooja; Lua, Lannah L.; Brar, Bobby; Froehlich, Mary; Planinic, Petar
Key Clinical Message: Ruptured cornual abscess or pyometra can resemble other more common causes of acute abdomen, including appendicitis, diverticulitis, tubo‐ovarian abscess, and perforated viscus. Despite its rarity, the diagnosis of ruptured pyometra should always be considered in females presenting with acute abdominal pain, particularly in the setting of a retained intrauterine device. Abstract : Ruptured cornual abscess or pyometra can resemble other more common causes of acute abdomen, including appendicitis, diverticulitis, tubo‐ovarian abscess, and perforated viscus. Despite its rarity, the diagnosis of ruptured pyometra should always be considered in females presenting with acute abdominal pain, particularly in the setting of a retained intrauterine device.